Enhancing Collaborative Dataset Exploration in VR: The Impact of Gaze Visualization on Tutors' Spatial Guidance and Communication - Khokhar, Adil; Borst, Christoph W.; Ami, Md Istiak Jaman; Heidarikohol, Niloofar (2025 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2025)
We investigate the effects of gaze visualization on instructional communication and effectiveness in a collaborative geosciences virtual reality (VR) environment. Our study provides new, specific insights into the effects of gaze visualization on guidance strategies, based on detailed communication analysis. Unlike prior research that employed simplified tasks (e.g., tangram puzzles or identifying symbols), we focused on realistic tasks involving the identification, alignment, and matching of 3D geo-terrain dataset features.In the study, subjects acted as tutors leading students (confederates blind to the condition) through three terrain interpretation tasks, locating, aligning, and matching geological terrain features, in a collaborative VR environment. The subjects performed tasks under two conditions: with and without live visualization of student gaze. We analyzed subjective ratings, task completion times, number of words spoken, and time spent looking at the student. Our findings indicate that gaze visualization not only reduces the overall time and verbal instructions required for corrective guidance, but also shifts the way participants provide guidance. This shift is reflected by fewer words used and shorter task completion times, suggesting a more efficient and visually oriented communication strategy. This suggests that gaze visualization enabled tutors to use more effective spatial guidance strategies thus reducing the reliance on extended verbal descriptions.